PREPARING NANOPARTICLES USING SOME BIOLOGICAL METHODS AND STUDYING THEIR EFFECT ON SOME MYCOTOXINS - Radhi, Zahraa Essa; Azeez, Zahraa Falah (Journal of Medical Genetics and Clinical Biology, 2024)
General Background: Mycotoxins, toxic substances produced by certain fungi and bacteria, pose significant health risks to humans and animals, necessitating effective remediation strategies. Specific Background: The use of environmentally friendly approaches to mitigate the impact of these toxins is crucial. Nanotechnology, particularly in conjunction with plant extracts, has emerged as a promising method for toxin remediation due to its cost-effectiveness and efficiency. Knowledge Gap: Despite the potential of nanomaterials in mycotoxin management, there is limited research exploring the interaction between plant extracts and nanotechnology in inhibiting toxin-producing fungi. Aims: This study aims to investigate the efficacy of zinc oxide nanomaterials synthesized from mint plant extracts in mitigating the effects of mycotoxins and inhibiting the growth of mycotoxin-producing fungi. Results: Mint leaves were collected from various locations in Al-Qadisiyah Governorate over an eight-week period. The extracted plant materials were used to synthesize zinc oxide nanoparticles, which demonstrated significant inhibitory effects on the growth of specific fungi responsible for mycotoxin production, thereby reducing mycotoxin formation. Novelty: This research highlights the innovative application of mint-derived zinc oxide nanoparticles as a dual-action agent—suppressing fungal growth while simultaneously preventing mycotoxin synthesis. Implications: The findings provide valuable insights into sustainable agricultural practices and mycotoxin management, paving the way for the development of natural, eco-friendly solutions to enhance food safety and protect public health.